UHPLC-MS profiles and antidiarrheal activity of Quercus coccinea münchh. and Quercus robur L. employing in vivo technique - Mady, Mohamed S.; Ibrahim, Reham R.; El-Sayed, Elsayed K.; El-Shazly, Mohamed; Chen, Lo-Yun; Lai, Kuei-Hung; El Shaarawy, Fatheya S.; Moharram, Fatma A. (Frontiers in Pharmacology, 2023)
Quercus L. genus (Oak) belongs to the family Fagaceae and their galls are used commercially in leather tanning, dyeing, and ink preparation. Several Quercus species were used traditionally in the management of wound healing, acute diarrhea, hemorrhoid and inflammatory diseases. The present study aims to investigate the phenolic content of the 80% aqueous methanol extract (AME) of Q. coccinea and Q. robur leaves as well as to assess their anti-diarrheal activity. Twenty-five and twenty-six polyphenolic compounds were tentatively identified in Q. coccinea and Q. robur AME, respectively using UHPLC/MS. The identified compounds are related to quercetin, kaempferol, isorhamnetin, and apigenin glycosides and their aglycones. In addition, hhydrolyzabletannins, phenolic acid, phenyl propanoides derivatives, and cucurbitacin F were also identified in both species AME of Q. coccinea (250, 500, and 1000 mg/kg) exhibited a significant prolongation in the onset of diarrhea by 17.7 %, 42.6%, and 79.7% respectively while AME of Q robur at the same doses significantly prolonged the onset of diarrhea by 38.6%, 77.3%, and 2.4 folds respectively as compared to the control. Moreover, the percentage of diarrheal inhibition of Q. coccinea was 23.8%, 28.57%, and 42,86% respectively, and for Q robur 33.34%, 47.3%, and 57.14% respectively as compared to the control group. Both extracts significantly decreased the volume of intestinal fluid by 27%, 39.78%, and 50.1% for Q coccinea respectively; and by 38.71%, 51.19%, and 60% for Q robur respectively as compared to the control group. In addition, AME of Q. coccinea exhibited a peristaltic index of 53.48, 47.18, and 42.28 with significant inhibition of gastrointestinal transit by 18.98%, 28.53%, and 35.95 % respectively; while AME of Q robur exhibited a peristaltic index of 47.71, 37, and 26.41 with significant inhibition of gastrointestinal transit by 27.72%, 43.89%, and 59.99% respectively as compared with the control group. Notably, Q. robur showed a better antidiarrheal effect in comparison with Q. coccinea and, the highest effect was observed for Q. robur at 1000 mg/kg as it was nonsignificant from the loperamide standard group in all measured parameters.